STUDI KOMPERATIF GAYA KEPEMIMPINAN KEPALA MTs.NEGERI DAN KEPALA MTs. SWASTA DI KABUPATEN MAJALENGKA - Herijeni (Pascasarjana Unviersitas Majalengka, 2021)
This research is motivated by the inequality in leadership style behavior between the Head of State MTs. and Head of MTs. Private, presumably due to differences in status. This study aims to determine: a) The types of leadership styles commonly used by the Head of State Madrasah Tsanawiyah; b) Types of leadership styles commonly used by Private Madrasah Heads; and: c) The difference in the quality level of leadership style between the Head of Public Madrasah Tsanawiyah and the Head of Private Tsanawiyah Madrasah in managing their respective madrasah. The study used a qualitative approach, the main data collection techniques and tools used in-depth interviews with purposive selected informants coupled with a questionnaire. Data were analyzed descriptively interpretive through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) The type of leadership style of the head of MTs. The country is more dominant in using a directing leadership style, characterized by always giving specific directions to subordinates; b) The type of leadership style of the Head of MTs. The private sector is more dominant in using the coaching leadership style, which is characterized by being very intense in training subordinates; c) There are differences in the level of quality of the leadership style of the Head of MTs. State and private, according to respondents' perceptions of the leadership style of the Head of MTs. Private sector is better than the head of MTs leadership style. Country.